Selected Aspects of Protectionism of EU Member States in the EU Agri-Food Market - Renata Grochowska; Adam Ambroziak (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Tendencies in national actions against foreign products currently observed in the European Union indicate protectionism or at least discrimination. The aim of this article is describe economic mechanisms of applying selected import-related policy instruments of Member States and to identify some potential directions of their impact on the functioning of the EU agri-food internal market. The presented mechanisms are related to three situations: (a) hindering the market entry through retargeting of consumer demand; (b) promotion of own products contrary to the fair rules of competition; (c) limiting economic activity of foreign companies. The analyses carried out allowed to identify economic activity areas, where negative effects could reveal and to state that the potential result of these activities may be selective reduction of trade or change of its directions.